The Role of Indonesian Muslim Student Action Unit (KAMMI) as Election Monitors in Improving Supervisory Integrity in the 2019 General Election in the City of Banjarmasin - Alfikri; Kurdi, Sulaiman (Fakultas Syariah UIN Antasari, 2024)
This research was conducted in Banjarmasin City against the backdrop of the large number of election violations and the large number of polling stations that must be monitored in the 2019 elections in Banjarmasin City. KAMMI as an election monitor involves itself in this supervision so that the election runs in accordance with the principles of the election. Election monitors can detect potential violations, provide confidence to the public regarding the validity of the results, and encourage accountability of election organizers. The existence of election monitors is also a form of social control that helps strengthen the foundations of democracy and increase active citizen participation in elections. This study aims to determine the role of the Indonesian Muslim Student Action Unit (KAMMI) as an election monitor in improving the integrity of supervision in the 2019 elections in Banjarmasin City, then to find out how the obstacles were faced. The type of research used is field research, by examining the circumstances and phenomena more clearly about the situation that occurs in the field. The research approach is a qualitative approach with qualitative descriptive methods. Data sources are informants totaling 9 people and documentation. Analysis of the results of this study was carried out by analyzing the data collected and presented in the form of descriptive descriptions. Then the researcher makes a conclusion and recommendation on the research results. The results showed that KAMMI played an adequate role as an extension of Bawaslu in monitoring the 2019 elections in Banjarmasin City. KAMMI carries out its duties according to the rules and code of ethics, is neutral, provides education to the public, and supports the participation of persons with disabilities. KAMMI faces obstacles in monitoring the 2019 elections in Banjarmasin City, including limited number of members, unstructured programs, and limited funds. Other internal factors include the focus of monitoring only on election day. External constraints include a lack of cooperation with Bawaslu Banjarmasin City, a lack of coordination between South Kalimantan Province Bawaslu and Banjarmasin City Bawaslu, and an unstructured coordination schedule. Despite the obstacles, KAMMI managed to improve the integrity of election monitoring. KAMMI's involvement as a political monitor can be a motivation for other institutions, although improvements are needed to overcome obstacles in the future.